1988
DOI: 10.2170/jjphysiol.38.199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noradrenaline on plasma hormones and metabolites in cold-acclimated rats.

Abstract: The effects of noradrenaline (NA) injection (40µg/100g, i.p.) on plasma glucagon, corticosterone (CS), deoxycorticosterone (DOCS), glucose, and free fatty acids (FFA) were investigated in cold-acclimated rats (CA) and warm controls (WC). The CA were transferred to warm control temperature ca. 18 h prior to NA or saline injection. The animals were decapitated and the trunk blood was collected 0, 10, 20, and 40 min after the injection. Plasma glucagon level increased significantly during the experimental period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
3
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
3
3
0
Order By: Relevance
“…The increase of BAT weight did not differ between ICE and CA, although the increases in fat-free dry matter fraction and glucagon level of BAT were smaller in ICE than in CA. A possible role of glucagon in metabolic cold acclimation has been recently reported from our laboratory (KuROsHIMA et al, 1978(KuROsHIMA et al, , 1984(KuROsHIMA et al, , 1988 and also others (BILLINGTON et al, 1987;HOWLAND and BOND, 1987). The present study confirmed the previous results that glucagon level was higher in BAT from CA even in the resting state (HABARA and KUROSHIMA, 1983;, suggesting that glucagon exerts its thermogenic effect on BAT in high concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of BAT weight did not differ between ICE and CA, although the increases in fat-free dry matter fraction and glucagon level of BAT were smaller in ICE than in CA. A possible role of glucagon in metabolic cold acclimation has been recently reported from our laboratory (KuROsHIMA et al, 1978(KuROsHIMA et al, , 1984(KuROsHIMA et al, , 1988 and also others (BILLINGTON et al, 1987;HOWLAND and BOND, 1987). The present study confirmed the previous results that glucagon level was higher in BAT from CA even in the resting state (HABARA and KUROSHIMA, 1983;, suggesting that glucagon exerts its thermogenic effect on BAT in high concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Figure 1 shows the changes in plasma glucagon levels after NA injection. The result was essentially the same as reported previously (KUROSHIMA et al, 1988). The initial level was significantly lower in CA.…”
supporting
confidence: 92%
“…It was noted in the present study that plasma glucagon level was restored to the initial level in WC during the experimental period for 40 min, while it remained still higher than the initial level in CA. This finding, together with the previous one (KUROSHIMA et al, 1988) clearly indicates an enhanced action of NA on glucagon release, suggesting a possible involvement of this pancreatic hormone secreted by NA in an enhanced NST in concert with NA during cold acclimation.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Adaptation to cold stress involves, among other things, glucocorticoid production and sustained activation of the sympathetic nervous system (Leduc, 1961; Shum et al, 1969; Yahata et al, 1987; Kuroshima et al, 1988; Ohno et al, 1990; Gordon, 1993; Harper and Austad, 2000; Cannon and Nedergaard, 2004, 2011; Feldmann et al, 2009; Baccan et al, 2010). The immunosuppressive effects of glucocorticoids are widely appreciated, and activation of the sympathetic nervous system has broad effects beyond driving adaptive thermogenesis and supporting processes such as heart rate and cardiac output.…”
Section: Cold and Dampening Of The Immune Systemmentioning
confidence: 99%